Orthogonal Kravchuk’s polynomials - Prizva , G. I. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A survey of the principal works of Academician M. P. Kravchuk and his students in the area of orthogonal polynomials of a discrete variable is presented. The value of these studies for the further development of the theory, for drawing generalization, and for the construction of different applications of this class of special functions is noted.